2020
DOI: 10.5415/apallergy.2020.10.e36
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic procedures & practices in drug allergy/hypersensitivity: a survey of 13 Asian countries

Abstract: Background: The issues and challenges in the diagnosis of drug allergy/hypersensitivity among children and adults in Asia are likely to be different from non-Asian countries. Objective: To study the diagnostic modalities used in the evaluation and management of drug allergy/drug hypersensitivity reactions (DHRs) among member societies of the Asia Pacific Association of Allergy, Asthma and Clinical Immunology (APAAACI). Methods: A questionnaire comprising 41 questions was circulated electronically to member soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 68 publications
0
8
0
1
Order By: Relevance
“…It is important to note that a recent survey identified a knowledge gap among pediatric neurologists in recognition of racial/ancestral differences in carbamazepine‐related SJS/TEN risk 78 . Similarly, a survey among members of the Asia Pacific Association of Allergy, Asthma and Clinical Immunology societies revealed that only 25% of responders stated that HLA testing was mandatory before prescribing carbamazepine, and only 8.3% prior to prescribing allopurinol 79 . Despite strong evidence and recommendations reinforcing the increased risk of severe HSR in Asians, there is still a lack of clinical uptake and knowledge surrounding this risk.…”
Section: Human Leukocyte Antigen: the Untapped Hotspot For Pharmacogenomic Actionability?mentioning
confidence: 99%
“…It is important to note that a recent survey identified a knowledge gap among pediatric neurologists in recognition of racial/ancestral differences in carbamazepine‐related SJS/TEN risk 78 . Similarly, a survey among members of the Asia Pacific Association of Allergy, Asthma and Clinical Immunology societies revealed that only 25% of responders stated that HLA testing was mandatory before prescribing carbamazepine, and only 8.3% prior to prescribing allopurinol 79 . Despite strong evidence and recommendations reinforcing the increased risk of severe HSR in Asians, there is still a lack of clinical uptake and knowledge surrounding this risk.…”
Section: Human Leukocyte Antigen: the Untapped Hotspot For Pharmacogenomic Actionability?mentioning
confidence: 99%
“…DHRs represent a significant public health problem with a prevalence of 10-20% in hospitalized patients and up to 7% in the general population exposed to drugs [76]. Tang et al surveyed the diagnostic modalities used in the evaluation and management of DHRs among member countries of the Asia Pacific Association of Allergy, Asthma and Clinical Immunology (APAAACI) which included respondents from five Southeast Asian countries [77]. The authors reported that HLA genotype testing before prescribing carbamazepine, allopurinol, and abacavir was not mandatory or recommended by local pharmacy regulatory agencies in the majority of countries despite strong associations for SCARs with Asian ethnicity.…”
Section: Dhrs In Southeast Asia: Regional Issues and Challengesmentioning
confidence: 99%
“…The Asia Pacific Association of Allergy, Asthma and Clinical Immunology (APAAACI) is actively involved in the science and education of allergy, regional data generation and publications of white papers (white paper on climate change) [ 4 ] and surveys (drug allergy) [ 5 ] on various health and disease areas including asthma, immunotherapy, food allergy, microbiome etc., consensus documents, its educational e-learning’s, web lectures, scientific publications in our Asia Pacific Allergy journal, scientific collaborations, training workshops and symposia and participation in global guidelines through partnerships with sister organizations. Through these we are building a framework to meet the challenge of the rising complexity of allergies in the Asian Pacific region…”
mentioning
confidence: 99%